Experiences of Lecturers in Conducting Laboratory Clinic Practicum of Emergency and Crtitical Care Nursing in the Covid-19 Pandemic - Sukraandini Ni Komang; Sang Ayu Ketut Candrawati (MBUnivPress, 2021)
Indonesia is one of the countries that has been confirmed to the Corona virus pandemic (Covid-19). The government have been making a policy to prevent of corona cases in Indonesia such as social distancing or physical distancing recommendations. One of the policy programs related to Physical Distancing in the education is that it requires lecturers to carry out the teaching and learning process at home. This policy is of course a challenge for nursing education institutions to continue to increase their role in providing a comfortable learning environment and appropriate learning methods in the corona virus pandemic (Covid-19) situation. Laboratory learning (skills lab) is an important part of a complex educational process and must be integrated in all educational programs that refer to the curriculum, especially the achievement of competencies for students. The method of this study was qualitative descriptive research the population of this study was lecturers who had experience in teaching Critical Concise Practicum Laboratory Skills. The sample in this study amounted to 4 participants. The results obtained 4 themes, namely: (1) unpredictable situation, (2) unable to directly assess the response (3) internet signal as an obstacle (4) efficient in the teaching and learning process.